The Stigma of Abortion among Adolescent Girls in the Community: A Qualitative Study in North Lampung District, Indonesia - Fitarina, Fitarina; Ningshih, Yuliati Ampera; Krismaningrum, Hasti Primadilla (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2024)
Introduction: Adolescent abortion remains a contentious moral dilemma in Indonesia. The choice to have an abortion is due to enduring an unwanted pregnancy, despite the stigma of abortion from society. Purpose: The study focused on assessing abortion stigma information and attitudes toward abortion among adolescent girls. Methods: Descriptive qualitative study using survey method was the research design. 450 participants from junior high school, high school and university students were recruited. Data were collected by survey technique using a questionnaire adapted from the Stigma Attitude, Believe of Absortion Scale (SABAS). Data were analyzed quantitatively using frequency distribution and qualitatively to evaluate young women's attitudes towards abortion by grouping data and problem trees. Results: Participant characteristics 100% had no abortion experience and 88% were not dating, 98% of adolescent girls had a high stigma scale. Stigma content identified included cruelty, stupidity, sin, sad, risk of psychosocial and health problems. Adolescents also expressed positive sentiments related to concern and empathy for women experiencing unfortunate situations, either due to rape or health emergencies. Conclusion: Adolescent girls stigmatized the act of abortion and also cared about victims in unfortunate situations. Efforts are needed to make the community understand the stigma of abortion which has a psychological and social impact on adolescents by increasing socialization. It is important for adolescent girls to be educated through sexual education and to prevent unwanted pregnancies and abortions. Family and community empathy for adolescents by providing affection, especially for adolescent girls to have reproductive readiness or safe pregnancy. Latar Belakang: Aborsi pada remaja masih menjadi dilema moral yang terus diperdebatkan di Indonesia. Pilihan melakukan aborsi disebabkan menanggung kehamilan tidak diinginkan, walaupun ada stigma abortus dari masyarakat. Tujuan: Penelitian berfokus pada mengkaji informasi stigma abortus dan sikap menghadapi aborsi pada remaja putri. Metode: Studi kualitatif deskriptif menggunakan metode survey meru[akan desain penelitian ini. Merekrut 450 partisipan dari Siswa Sekolah Menengah Pertama, Sekolah Menengah Atas dan Mahasiswa Perguruan Tinggi. Data dikumpulkan dengan teknik survei menggunakan kuesioner diadaptasi dari Stigma Attitude, Believe of Absortion Scale (SABAS). Data dianalisis secara kuantitatif menggunakan distribusi frekuensi dan kualitatif untuk mengevaluasi sikap remaja putri terhadap abortus dengan mengelompokkan data dan pohon masalah. Hasil: karakteristik partisipan 100% tidak memiliki pengalaman aborsi dan 88% tidak pacaran, 98% remaja putri memiliki skala stigma tinggi. Isi stigma yang teridentifikasi meliputi kekejaman, kebodohan, dosa, menyedihkan, berisiko terjadi masalah psikososial dan kesehatan. Remaja juga mengungkapkan sentimen positif terkait keprihatinan dan rasa empati terhadap perempuan yang mengalami situasi yang tidak menguntungkan, baik karena pemerkosaan maupun kegawatan kesehatan. Simpulan: Remaja Putri memberikan stigma terhadap tindakan aborsi dan juga sikap peduli terhadap korban yang berada pada situasi tidak menguntungkan. Perlu upaya memahamkan kepada komunitas tentang stigma abortus yang berdampak psikologis dan social kepada remaja dengan peningkatan sosialisasi. Remaja putri penting diberikan edukasi melalui pendidikan mengenai sexual dan untuk mencegah kehamilan yang tidak diinginkan, melakukan abortus. Keluarga dan komunitas empati pada remaja dengan memberikan kasih sayang, khususnya pada remaja putri untuk memiliki kesiapan reproduktif atau hamil yang aman.